Determination of Complete Sequence Mutation of Myostatin Gene in Fast- and Slow-Growing Chicken - Isyana Khaerunnisa; Ahmad Furqon; Saiful Anwar; Jakaria Jakaria; Cahyo Budiman; Irma Isnafia Arief; Cece Sumantri; Yong Soo Kim (Bogor Agricultural University, Indonesia, 2023)
Myostatin plays a role in inhibiting skeletal muscle growth in vertebrates. This study aimed to investigate the full sequence of the myostatin gene in fast-growing and slow-growing chickens. Fast- and slow-growing chicken models were produced from F2 Kampung x broiler. The full sequence of the myostatin gene was identified using 24 pairs of primers covering about 8,000 bp. mRNA expression analysis of muscle tissue was performed to examine whether the expression levels of myostatin are affected by chicken lines, sex, or muscle type. The results showed 170 mutations in fast- and slow-growing chickens. One hundred and sixty-one of them are novel mutations. A total of five and twenty-two alleles were specific alleles found only in the fast-growing and slow-growing groups of chickens, respectively. There were no differences in amino acids and gene expression levels of myostatin between the fast- and slow-growing chickens. In summary, the results of this study showed that specific alleles for the fast-growing or slow-growing chicken groups were found, suggesting that these specific alleles potentially be used as genetic markers for muscle growth in chickens.